Smart Prescription Reader: Enhancing Accuracy in Medical Prescriptions - Yulianto, Ragil (Institut Riset dan Publikasi Indonesia, 2025)
Reading a doctor's handwritten prescription is a challenge faced by most patients and some pharmacists, which in some cases can lead to negative consequences due to misinterpretation of the prescription. The